2014
DOI: 10.4155/bio.14.37
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Biotherapeutics with Endogenous Counterparts and Pre-Existing Antibodies: an Interferon Case Study

Abstract: Prescreening of serum to exclude reactive individuals resulted in successful cross-validation and the establishment of a high integrity pharmacokinetic assay in support of global clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 7 publications
0
12
1
Order By: Relevance
“…It should be noted that other studies have shown pre-existing AIAb rates to be higher than what was observed in this testing [16]. Sample means were 79 (NHS) and 84 (HCV), and standard deviations were similar, 18 (NHS) and 24 (HCV).…”
Section: Cut Pointcontrasting
confidence: 45%
See 1 more Smart Citation
“…It should be noted that other studies have shown pre-existing AIAb rates to be higher than what was observed in this testing [16]. Sample means were 79 (NHS) and 84 (HCV), and standard deviations were similar, 18 (NHS) and 24 (HCV).…”
Section: Cut Pointcontrasting
confidence: 45%
“…Negative control is prepared by pooling individual normal human serum screened in the PK and ADA assays to eliminate reactive individuals, those with endogenous interferon Lambda and/or pre-existing antibodies [16]. Positive control is prepared at the LPC (50 ng/ml) and HPC (500 ng/ml) by spiking the AGP4 IgM APAb (Sinica) into the NHS pool described above.…”
Section: Bridge Apab Assaymentioning
confidence: 99%
“…The bioanalytical assays consisted of several independent measures of the ADC including: T-Ab, A-ADC, T-ADC, antibody conj-payload and unconj-payload; soluble target, a panel of biomarkers indicative of programed cell death and a series of immunogenicity assays designed to elucidate ADA specificity [13][14][15] and clinical impact [16][17][18], as described in Table 1. The A-ADC and the conjugated active payload assays were presumed to be most relevant to bioactivity.…”
Section: Resultsmentioning
confidence: 99%
“…Assay specificity is described in detail in Myler et al . . The Lambda detection assay is cross‐reactive with the endogenous lambda counterpart.…”
Section: Bioanalytical Methodsmentioning
confidence: 99%